COMPARISON BETWEEN ONLAY AND SUBLAY METHOD OF MESH REPAIR FOR INCISIONAL HERNIA - Khan, Nadia Saeed; Iqbal, Syed Abdullah; Shaikh, Bashir Ahmad; Baqai, Fareeduddin (Journal of Postgraduate Medical Institute, 2014)
Objective: To evaluate the repair of incisional hernia by two different methodsonlay (Conventional method) and sublay(retromuscular preperitoneal)methods at two different tertiary care centres of Karachi - Pakistan. Methodology: Patients diagnosed clinically and confirmed ultrasonographicallyand subsequently operated upon with either methods were included inthis study. The primary endpoint was hernia recurrence. Secondary endpointswere operative time, length of hospital stay and postoperative complicationsof the two methods. Results: A total of 80 patients were allocated in two groups, group A (n=40)underwent incisional hernia repair by sublay method and the remaining inGroup B, (n=40) by onlay method. The frequency of wound infection wasfound significantly higher in the Sublay method of mesh placement (p=0.019).The frequency of seroma formation was significantly higher in the onlay methodof mesh placement(p=0.076). Conclusions: The sublay technique was proven to be very effective, with minimalcomplications and low recurrence rate.